1998
DOI: 10.1007/s004420050596
|View full text |Cite
|
Sign up to set email alerts
|

Increase in a heat-shock protein from blood cells in response of nestling house martins ( Delichon urbica ) to parasitism: an experimental approach

Abstract: Heat-shock proteins (HSPs) are synthesized by animals and plants in response to various stressors. The level of the HSP60 stress protein was measured from the cell fraction of peripheral blood obtained from nestling house martins (Delichon urbica) to test whether ectoparasitism increased the concentration of stress protein. We assessed HSP from nestlings raised in nests previously treated with an insecticide or infested with 50 martin bugs (Oeciacus hirundinis). In addition, haematozoa infections were checked … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
49
1

Year Published

1999
1999
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 61 publications
(50 citation statements)
references
References 21 publications
0
49
1
Order By: Relevance
“…This is not surprising because in an experiment consisting of a reduction in the intensity of infection by Haemoproteus and the prevalence of infection by Leucocytozoon in female blue tits, Tomás et al (2005) found that control females had a higher Wnal level of HSP60 than medicated ones. Also, other studies on birds suggested a role of this protein in responses to parasitism (Merino et al 1998;Merino et al 2002;. Parasites may cause increases in HSP60 by at least three diVerent, non mutually exclusive mechanisms: it could be a response to the fever occasioned by the infection, i.e.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This is not surprising because in an experiment consisting of a reduction in the intensity of infection by Haemoproteus and the prevalence of infection by Leucocytozoon in female blue tits, Tomás et al (2005) found that control females had a higher Wnal level of HSP60 than medicated ones. Also, other studies on birds suggested a role of this protein in responses to parasitism (Merino et al 1998;Merino et al 2002;. Parasites may cause increases in HSP60 by at least three diVerent, non mutually exclusive mechanisms: it could be a response to the fever occasioned by the infection, i.e.…”
Section: Discussionmentioning
confidence: 99%
“…These proteins prevent cellular homeostasis alteration and are involved in many diVerent functions like protein synthesis, folding and transport, as well as in degradation of misfolded, non-functional proteins (Morimoto 1991). These proteins are implicated in responses to a wide array of stressors including blood parasites (Merino et al 1998;Tomás et al 2005). As previously reported (Merino et al 2002;Tomás et al 2005), we did not Wnd Haemoproteus infection intensity signiWcantly associated with levels of HSP70.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, avoidance of blood feeding through the circulation of biochemicals in the blood stream may reduce the feeding efficiency of parasites (Wikel 1996). This is the case for immunoglobulins (Wang et al 1998) and potentially also for heat shock proteins that can be induced by the presence of ectoparasites (Merino et al 1998). Finally, hosts may avoid blood feeding by ectoparasites through the production of hypersensitivity reactions and T-cell immune responses (Roitt et al 1996;Saino et al 1997).…”
Section: Introductionmentioning
confidence: 95%
“…Third, HSPs, despite their highly conserved nature, may be very immunogenic (Del Giudice 1994). These vital functions have led to the use of HSPs as: markers of injurious stress in disease (Macario 1995;Martinez et al 1999a;Merino et al 1998) and in drug ecacy studies (Tosi et al 1997) and ecotoxicological studies (Eckwert et al 1997); and as constituents of vaccines (Newport 1991). In a recent study on HSP60, HSP70 and HSP90 expression in organs of rats with a secondary Trichinella spiralis infection (Martinez et al 1999b), we have established that such rats, contrary to primary-infected rats (Martinez et al 1999a), exhibit no increased expression of test HSP.…”
Section: Introductionmentioning
confidence: 96%